A Light-Controlled TLR4 Agonist and Selectable Activation of Cell Subpopulations - Stutts, Lalisa (Chembiochem, 2015)
Spatial and temporal aspects of immune cell signalling are key parameters in defining the magnitude of an immune response. Toll-like receptors (TLRs) on innate immune cells are important in early detection of pathogens and initiation of an immune response. Controlling the spatial and temporal signalling of TLRs would enable further study of immune synergies and assist in the development of new vaccines. Here, we show a light-based method for spatial control of TLR4 signalling. A TLR4 agonist, pyrimido[5,4-b]indole, was protected with a cage at a position critical for receptor binding. This afforded a photo-controllable agonist that was inactive while caged, yet effected NF-κB activity in cells following UV photo-controlled deprotection. We demonstrated spatial control of NF-κB activation within a population of cells by treating all cells with the caged TLR4 agonist and constraining light exposure, thereby activation, to a region of interest.